Fuzzy Logic Based Interline Unified Power Quality Conditioner for Voltage Regulation of Critical Load Bus - Nithya Sree, N; Srinivasa Varma, P (International Journal of Engineering and Technology, 2018)
Interline unified power quality conditioner is the recent advancement in the world of FACTS devices and technology. The new equipment is only a mere extension of the existing FACTS device featuresÂ  like Distributed Static Compensator which does not limit to better voltage regulation at the gird side as well as load side bus. The effectiveness of the new FACTS device is compared with its homologous counterpart, namely conventional Unified power quality conditioner. It is observed that there is significant difference with respect to the arrangement of parallel and series connected converters. Soft computing technique namely fuzzy logic based controller for the proposed Interline unified power quality conditioner is presented in the paper. The implementation and usefulness of the proposed control topology is tested and simulated in MATLAB/SIMULINK environment.Â